Developing speed - Jeffreys, Ian (Sport performance series, 2013)
Athletes in all sports rely to greater or lesser degree on speed, whether it involves sprinting down the track or chasing a loose ball, speed often contributes to overall athletic ability. This guide offers scientific coverage of speed development, and helps in the assessment of current ability and identification of areas of greatest need